2020
DOI: 10.1146/annurev-control-081219-082713
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Methods in Robotics

Abstract: The goal of this article is to provide a thorough introduction to the state of the art in magnetic methods for remote-manipulation and wireless-actuation tasks in robotics. The article synthesizes prior works using a unified notation, enabling straightforward application in robotics. It begins with a discussion of the magnetic fields generated by magnetic materials and electromagnets, how magnetic materials become magnetized in an applied field, and the forces and torques generated on magnetic objects. It then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
178
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(178 citation statements)
references
References 143 publications
0
178
0
Order By: Relevance
“…The dipole approximation is also appropriate for nonspherical magnets when the operating distance exceeds two side lengths . This approximation may lose efficacy when the miniature robot is actuated at a short range, in which case other field computation methods need to be considered, such as finite element analysis (FEA) and multipole expansions …”
Section: Magnetic Actuation and Magnetic Fieldsmentioning
confidence: 99%
“…The dipole approximation is also appropriate for nonspherical magnets when the operating distance exceeds two side lengths . This approximation may lose efficacy when the miniature robot is actuated at a short range, in which case other field computation methods need to be considered, such as finite element analysis (FEA) and multipole expansions …”
Section: Magnetic Actuation and Magnetic Fieldsmentioning
confidence: 99%
“…As a result the magnetic agent will experience a torque that tends to rotate the agent into alignment with the field, and a force that pulls the agent according to the shape of the magnetic field. The magnetic force can be expressed linearly with respect to m (Abbott et al, 2020):…”
Section: Force and Torque On A Magnetic Agentmentioning
confidence: 99%
“…Given that there can be no stable magnetic equilibrium point in a static magnetic field based on Earnshaw's theorem, it can be concluded that any system designed to manipulate untethered levitating magnetic agents must use feedback control to stabilize the position of the agents (Abbott et al, 2020). The main contribution of this article is that it discovers the effect of magnetic inter-agent forces on 3D motion of multiple magnetic microrobots while manipulated by an underactuated system, based on which controllers are synthesized and validated to independently regulate the position of both types of particle and functional microrobots.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the complexity of internally actuated mechanisms results in cumbersome design and prevents a substantial cost reduction. Magnetically actuated endoscopes [16][17][18][19][20] have demonstrated the potential to reduce pain, reduce cost, enhance diagnostic capabilities 21 and improve therapeutic interventions. Although promising, translating magnetically actuated endoscopes for clinical use has failed due to control challenges.…”
mentioning
confidence: 99%